Virtual Reality in Treatment for Psychological Problems in First-Line Health Care Professionals Fighting COVID-19 Pandemic: A Case Series. Issue 10 (13th October 2022) - Pan, Xiao; Zhang, Ying-Cheng; Ren, Ding; Lu, Li; Wang, Yi-Hao; Li, Guan-Xiong; Xiao, Ying; Zhou, Hong-Yu; Bai, Yong-Hai
Abstract: Virtual reality therapy (VRT) is a new psychotherapeutic approach integrating virtual reality technology and psychotherapy. This case series aimed to study effectiveness of VRT in treating psychological problems. We described four cases of first-line health care professionals with emerging clinically significant early psychological problems during the COVID-19 outbreak, and specifically received the VRT treatment. We compared the Patient Health Questionnaire 9 items (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), PHQ-15, and Athens Insomnia Scale to evaluate psychological symptoms and sleep quality before and after sessions. All four cases showed a reduction in scale comparison. General scores of the PHQ-9 reduced 65%, GAD-7 reduced 52.17%, PHQ-15 decreased 38.17%, and scores of the Athens Insomnia Scale reduced 67.44%. Meanwhile, a reduction in depression, anxiety, psychosomatic, and sleeping symptoms was also found, which decreased 76.92% in general. These results are highly significant statistically. This case series demonstrated the effectiveness of VRT on psychological problems as a promising approach to apply on various psychological distress and disorders.